Adolescent alcohol exposure alters threat avoidance in adulthood - Landin, Justine D.; Chandler, Lawrence Judson (Frontiers in Behavioral Neuroscience, 2023)
The present study investigated the effects of binge-like alcohol exposure during adolescence on active avoidance in adulthood. Male and female rats were subjected to adolescent intermittent ethanol (AIE) exposure by vapor inhalation, and then tested in adulthood using a platform-mediated avoidance task. After training to press a lever to receive a sucrose reward, the rats were conditioned to a tone that co-terminated with a foot-shock. A motivational conflict was introduced by the presence of an escape platform that isolated the rat from the shock, but also prevented access to the sucrose reward while the rat was on the platform. During the task training phase, both male and female rats exhibited progressive increases in active avoidance (platform escape) in response to the conditioned tone, whereas innate fear behavior (freezing) remained relatively constant over training days. A history of AIE exposure did not impact either active avoidance or freezing behavior during task acquisition. On the test day following platform acquisition training, female rats exhibited higher levels of both active avoidance and freezing compared to male rats, while AIE-exposed male but not female rats exhibited significantly greater levels of active avoidance compared to controls. In contrast, neither male nor female AIE exposed rats exhibited alterations in freezing compared to controls. Following 5 days of extinction training, female rats continued to display higher levels of active avoidance and freezing during tone presentation compared to males. Male AIE-exposed rats also had higher levels of both active avoidance and freezing compared to the male control rats. Together, the results demonstrate that female rats exhibit elevated levels of active avoidance and freezing compared to males and further reveal a sex-specific impact of AIE on threat responding in adulthood.